Physiological and Biochemical Changes Associated with Hormonal Imbalance in Polycystic Ovarian Syndrome - Bibi Hajra Ishaq, Fatima Usama, Sadaf Gul, Mubashra Ali, Mubashra Tahir, Dur E Shehwar Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovarian syndrome is among the most prevalent endocrine diseases in women of reproductive age group. It is also typified by menstrual disorder, hyperandrogenism, anovulation, and polycystic ovarian structure. One of its pathogenesis is hormonal imbalance, which is a leading factor in reproductive, metabolic and cosmetic manifestataion. Objective: To evaluate hormonal imbalance associated with polycystic ovarian syndrome among women presenting to Mardan Medical Complex. Methods: The study was a descriptive cross-sectional study conducted in Mardan Medical Complex, Mardan, between January 2022 and June 2022. There were 78 women with polycystic ovarian syndrome. The information on demographic profile, clinical presentation, menstrual history, and findings of ultrasonographic was entered on a structured proforma. Hormonal analysis of blood (luteinizing hormone, follicle-stimulating hormone, LH/FSH ratio, testosterone, prolactin, thyroid-stimulating hormone, estradiol, and progesterone) was performed. The analysis of data was performed through the use of SPSS version 26. Quantitative variables were displayed in the form of mean ± SD whereas qualitative variables were shown using frequency and percentage. The tests of the associations were performed with chi-square test, and the p was accepted as significant (p=0.05). Results: The mean age of participants was 24.8 ± 4.6 years and the mean body mass index was 28.6 ± 4.9 kg/m². Menstrual irregularity was observed in 78.2% of women, while hirsutism, acne, and acanthosis nigricans were present in 59.0%, 50.0%, and 41.0%, respectively. Bilateral polycystic ovaries were found in 62.8% of cases. The most frequent hormonal abnormalities were raised luteinizing hormone in 56.4%, raised LH/FSH ratio in 52.6%, and elevated testosterone in 48.7% of participants. Significant associations were found between hormonal imbalance and obesity, menstrual irregularity, and hirsutism. Conclusion: Hormonal imbalance is a prominent feature of polycystic ovarian syndrome, with raised LH, elevated LH/FSH ratio, and increased testosterone being the most common abnormalities. Early hormonal assessment in women with PCOS is essential for timely diagnosis and better management of reproductive and metabolic complications. Keywords: Polycystic ovarian syndrome, hormonal imbalance, luteinizing hormone, testosterone, menstrual irregularity, hyperandrogenism